Ensuring health graduates' employability in a changing world: Developing interprofessional practice capabilities using a framework to inform curricula - Margo Brewer; Helen Flavell; Courtenay Harris; Melissa Davis; Katherine Bathgate (Journal of Teaching and Learning for Graduate Employability, 2014)
Background: Curtin University introduced an interprofessional first year curriculum in the Faculty of Health Sciences in 2011. This curriculum, delivered to over 2,300 first year health science students annually, consists of five common compulsory units, eight optional units (specific to several courses) and one discipline specific unit for each course. Significantly, the learning outcomes are informed by an Interprofessional Capability Framework (Brewer & Jones, 2013). Aim: Qualitative data from student reflective journals in one of the large common units was analysed to determine whether the use of a capability framework supported the development of the desired interprofessional capabilities. Method: The sample consisted of 105 of the 411 students enrolled in one of the common units (response rate 25.6 percent) in the second major teaching period (semester two) in 2011. The data was analysed via NVivo8© to provide a holistic view of the content of the reflections as they related to the Interprofessional Capability Framework. Results: The results indicate that the use of the Interprofessional Capability Framework in structuring the learning outcomes has influenced student learning. For example, ‘Client centred’ was the most frequently coded theme, followed by Collaboration, Team Function, and Quality Care. The results and weightings reflected the Framework. Conclusions: The framework guided this foundational interprofessional unit; the learning outcomes included key elements of the framework, the learning experiences were designed to meet these outcomes, and the assessment utilising a reflective journal was designed to measure the development of novice interprofessional capabilities.